Analysis of Isotropy and Uniformity of the Distribution of Reinforcing Phase in Cu/SiC Composite Materials Using μCT Methods - Katarzyna Pietrzak; Andrzej Gładki; Agata Strojny-Nędza; Tomasz Wejrzanowski; Kamil Kaszyca (Image Analysis and Stereology, 2021)
Tomography allows embedding of one space in another, especially ℛ2 → ℛ3, and observation of the nature of the volumetric internal composite structure. Now, not only a simple interpretation is expected of geometry defined via single thresholds of structures. The binary segmentation used for numerical structure analysis requires more detailed presentation. This paper shows an example of image analysis techniques applied to study the homogeneity of two-phase material. Using tomography analysis, the results of the homogeneity of the SiC particles with 10vol.%, 20vol.%, 30vol.%, 40vol.% volumetric bulk density of Cu/SiC composites are presented. Finally, for two independent coordinate systems, the distribution of  SiC particle masses and their total moments of inertia were determined. The results confirmed that for well-mixed composite powders the homogeneity of the reinforcing phase is expected in samples with a  SiC volume near 30vol.%. In this case, segregation by translation and rotation of SiC particles in the matrix, during the sintering process is restricted.